Competence aspects in forensic expertise of documents - Cataraga, Olga; Alămoreanu, Sorin; Petkovich, Petr (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The technical expertise of documents, although it already seems to be a well-developed field, in the current stage faces many problems which need to be investigated. This especially concerns the limits of expert-examiners’ competences. Apart from the “classic” means of falsifying and counterfeiting documents, new ones constantly appear as the offenders gain new skills and equipment, which makes expertise much more complex.In the present article, the authors attempt to discuss the limits of competences in the specialties of judicial expertise – code 6.01 (technical expertise of documents) and code 10.11 (examination of materials, documents, and writings). Exceeding one’s competence in carrying out the expertise cancels the evidence accumulated through scientific effort as well as entails disciplinary and often criminal liability of the expert-executor. The authors also propose an exemplary curriculum for training experts in forensic expertise of materials and documents and writings.
Keywords: technical expertise of documents; limits of competences; expert examiners; training experts; examination of materials; documents and writings; integrated conclusions